The World Bank's health projects in Timor-Leste: The political economy of effective aid - Andrew Rosser; Sharna Bremner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The World Bank's health sector projects in Timor-Leste - the Health Sector Rehabilitation and Development Project and the Second Health Sector Rehabilitation and Development Project - have been among the few successful operations it has funded in that country. This paper examines the factors underpinning their relative success and considers the wider lessons of the Bank's experience for our understanding of the conditions that lead to effective aid in fragile contexts. Much commentary on these projects has suggested, either implicitly or explicitly, that good design and management were key factors in their success. We argue that political economy factors also played an important role, extending and revising an earlier analysis. In particular, we suggest that these rehabilitation and development projects benefitted from (i) a political economy context that was relatively conducive to aid effectiveness in general and (ii) the fact that there was relatively little elite resistance to the World Bank's health policy agenda compared to its policy agenda in other sectors. In terms of wider lessons, we argue for a more political understanding of the determinants of aid effectiveness. Specifically we suggest that aid effectiveness needs to be seen as a function not just of the technical quality of project design and the administrative competence of project managers but also the extent to which there is congruence between donor and local elites' agendas.
Keywords: I18; O21; 330; Timor-Leste; aid effectiveness; fragile contexts; health; World Bank